'My favourite meme page': Balenciaga's Instagram account and audience fashion labour online. (1st October 2021) - Skjulstad, Synne
As fashion 'goes viral', adapting to digital popular cultural flows, streams, image aggregations and memes, there is a need for better grasping how these platforms feed into the aesthetics of mediations of fashion. Contemporary digitally mediated fashion is conditioned by what van Dijck and Poell refer to as a new media logic, one that permeates the 'strategies, mechanisms, and economics underpinning these platforms' dynamics'. This logic includes audience labour. This article focuses on how the audience is put to work and how such work becomes integral to the mediational aesthetic by using the Instagram account of Paris-based fashion brand Balenciaga as a heuristic device. In connecting perspectives from fashion and media studies, this article discusses how fashion mediation is entangled in processes that harness audience labour on Instagram. Balenciaga takes on communication strategies that expose the aesthetics of user engagement. On Instagram, the brand presents its take on fashion photography in the digital age as part of its visual identity on this platform. Furthermore, in feeding the comments section, users participate in 'boundary maintenance', separating Balenciaga insiders from outsiders who lack knowledge of the perpetually changing aesthetic codes of fashion imagery. Online audiences thus find themselves at the crossroads of consumption, production and gatekeeping.